2019
DOI: 10.3748/wjg.v25.i21.2603
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology approach reveals protective mechanisms of Jian-Pi Qing-Chang decoction on ulcerative colitis

Abstract: BACKGROUND Given the complex pathogenesis of ulcerative colitis (UC), the conventional therapeutic methods are not fully curative. As a sort of systematic complementary and alternative medicine, traditional Chinese medicine (TCM) provides new options for the standard therapy. Nevertheless, there are still numerous problems with the promotion of TCM attributed to its complexity, and consequently, new research approaches are urgently needed. Thus, we explored the protective effects of Jian-Pi Qing-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…It is reported that JPQCD (17.1 g/kg) treatment reduces the mRNA levels of IL-1β, IL-8, TNF-α and NF-κB in DSSinduced UC mice, suppresses activation of NF-κB and increases phosphorylation of IκB [140]. Using systems pharmacology to predict the active ingredients, it shows that 170 targets for the 107 active ingredients of JPQC and 112 candidate targets of UC, and JPQC treatment can improve the mucosal inflammatory response and intestinal epithelial barrier function via the NF-κB/ HIF-1α signaling pathway [141].…”
Section: Heat-clearing and Drying Dampness Categorymentioning
confidence: 99%
“…It is reported that JPQCD (17.1 g/kg) treatment reduces the mRNA levels of IL-1β, IL-8, TNF-α and NF-κB in DSSinduced UC mice, suppresses activation of NF-κB and increases phosphorylation of IκB [140]. Using systems pharmacology to predict the active ingredients, it shows that 170 targets for the 107 active ingredients of JPQC and 112 candidate targets of UC, and JPQC treatment can improve the mucosal inflammatory response and intestinal epithelial barrier function via the NF-κB/ HIF-1α signaling pathway [141].…”
Section: Heat-clearing and Drying Dampness Categorymentioning
confidence: 99%
“…However, there were also studies that suggest that HIF-1 α contributes to pathological progress in gastrointestinal diseases. As has been reported, Jian-Pi Qing-Chang treatment attenuated the intestinal epithelial permeability and inflammation by inhibiting NF- κ B/HIF-1 α pathways in colitis mice [ 37 ]. Further, the interferon-gamma (IFN- γ ) induced intestinal epithelial permeability and disruption of the intestinal tight junction by activating HIF-1 α [ 38 ].…”
Section: The Role Of Hifs In the Gtmentioning
confidence: 90%
“…, MPO, interleukin (IL)-1β, IL-8, and tumor necrosis factor alpha (TNF-α)], and improve the barrier function of the intestinal epithelium. In addition, JPQCR can regulate DSS-induced abnormal intestinal motility in UC mice by inhibiting the cascade of intestinal inflammation and reducing autophagy in interstitial cells of Cajal[ 10 , 11 ]. Based on JPQCR, the Jianpi Qingchang Huashi Recipe (JPQCHSR) has newly added TCM drugs including Poria, Tangerine Peel, Coix Seed, Alisma, and Radix Scutellariae .…”
Section: Introductionmentioning
confidence: 99%